A study on dynamic non-destructive testing of ground anchorages - dynamic stiffness method (International Journal of Geoscience, Engineering and Technology, 2025)
This present paper analyzes an anchored retaining wall using a non-destructive dynamic test, which is based on the variation of the dynamic stiffness of the ground anchors, applied to a real case study. The main objective is to evaluate the applicability and particularities of the method to identify the structural integrity of the anchorages, including their free, total and anchored lengths, as well as their current working loads. The results indicated that the dynamic stiffness of the anchorages varied around 5.0E8 N/m, while the working loads found were values between 74.6 kN and 107.9 kN. The analyses performed indicated that the dynamic stiffness of the anchorages did not present large variations along the anchored wall, proving that the determined lengths accurately reflect the real situation of the anchorages. In addition, a very isonomic distribution of forces was obtained, evidenced by the stiffness values obtained. The method stood out for its practicality in execution and analysis of results, consolidating itself as an effective and non-destructive tool for structural evaluation. Despite the general ease of the method, the study reinforces the need for technical experience in the interpretation of specific steps of the procedure, especially in cases with more complex structural behavior. The test proved to be a reliable solution for the continuous monitoring and diagnosis of containment systems, meeting the requirements of normative inspections and contributing to preventive maintenance. Thus, the work reinforces the potential of the method to ensure the safety, structural performance and longevity of anchored walls.
Keywords: Integrity tests; Mechanical impedance; Anchorage monitoring